Twitter Users' Displays of Affect in the Global Warming Debate. (April 2022) - Cameron, Shanna; Russell, Alexandra; Brake, Luke; Fredlund, Katherine; Morris, Angela
This article engages with recent discussions in the field of technical communication that call for climate change research that moves beyond the believer/denier dichotomy. For this study, our research team coded 900 tweets about climate change and global warming for different emotions in order to understand how Twitter users rely on affect rhetorically. Our findings use quantitative content analysis to challenge current assumptions about writing and affect on social media, and our results indicate a number of arenas for future research on affect, global warming, and rhetoric.